Marketing Strategy for Pottery Products in Kesilir Village-Wuluhan-Jember Regency Through Digital Marketing Strategies Efforts to Overcome the Impact of the Covid-19 Pandemic - Rike Oktarianti; Dwi Setyati; Eva Tyas Utami; Anik Suwandari (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The Covid-19 pandemic that has been going on for more than a year has had a major impact on UMKM (micro, small, and medium enterprises). Most of the business actors experienced a decline in sales and some even had to close their businesses. This impact was also felt by pottery craftsmen in the village of Kesilir-Wuluhan, Jember, one of which was the MSME Lies pottery. These MSMEs have difficulty in marketing their products, so sales have decreased drastically, almost reaching 60%. Therefore, the purpose of this assisted village service program activity is to provide assistance in increasing the sales of pottery products with digital marketing strategy. The implementation of the digital marketing strategy begins with the development of pottery products that are tailored to consumer interests during the pandemic, such as various flower pots, souvenirs, kowi and other types of products. In addition, promotions are also carried out through social media such as Facebook and Instagram. Promotion strategy and online sales through Instagram, Shopee and marketplace on Facebook have a significant impact on increasing pottery sales turnover. The average monthly sales turnover either through shopee, marketplace or instagram and whatsapp in the last 6 months from March to August 2021 can reach around IDR 2,500,000-3,500,000.